Phylodynamic Analysis and Implication of HCV Genotype 4 Variability on Antiviral Drug Response and T-Cell Recognition - Giuseppina Maria Elena Colomba; Noemi Urone; Vito di Marco; Donatella Ferraro (Viruses, 2020)
Therapies for HCV care could change the prevalence and the geographic distribution of genotypes due to differences in Sustained Virologic Response (SVR). In this scenario, uncommon genotypes/subtypes, such as genotype 4, could spread from high-risk groups, replacing genotypes eradicated by antiviral drugs. Genotype eradication is also strongly influenced by the CD8+ T cell response. In this study, the genetic variability in HCV genotype 4 strains obtained from a cohort of 67 patients naïve to DAA therapy was evaluated. We found that the presence of resistance-associated substitutions (RAS) was able to affect drug responses. Next, using a prediction tool, viral mutations were identified by their ability, or lack thereof, to reduce the binding affinity with HLA, which affects T cell recognition. The Bayesian coalescent analysis suggested two different circulation clusters, one in risk groups (IDUs and MSM) and the other due to migration flows, dated to 1940 and 1915, respectively. Most of the RAS overlapped with HLA and a lack of binding mutations was observed in 96% of strains. This study describes the introduction of HCV genotype 4 in a region of the Mediterranean basin and evaluates how HCV genotype 4’s genetic variability could affect the response of antiviral drugs and CD8+ T cell recognition.